Menghidupkan Kembali Sastra Lama Bersama Nadia Omara Melalui Cerita Rakyat Kalimantan Selatan di Era Digital - Nabila Ramadhani Putri (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2025)
This study aims to examine how Nadia Omara as a digital content creator plays a role in reviving old literature, especially South Kalimantan folklore, through digital media. Using a descriptive qualitative approach and case study method, data was collected through observations of Nadia Omara's digital activities on platforms such as YouTube, Instagram, and TikTok. This study analyzes the adaptation strategies used by Nadia Omara to make folklore more relevant and interesting for the younger generation. The results of the study show that digital media is not only a means of preservation, but also revitalization of traditional literature. The narrative, visual, and communication style strategies used by Nadia Omara are able to bridge old culture with the modern digital world, as well as build new interest in the richness of regional culture.